Education for human rights and human security (Research, Society and Development, 2022)
Human Rights are those indispensable and inviolable that must be guaranteed to all individuals, such as the right to life, nutrition, education, freedom, among many others. Human Security, on the other hand, is the search for freedom from fears and needs, where the human being, and not the State, is at the center of the security debate. When one observes education in relation to Human Security and Human Rights, the humanitarian role of education is evident, given its formative role. With this work, we seek to understand how these concepts are related. In order to do so, a qualitative review of the literature was carried out, selecting works through exploratory reading in search of the useful essence related to the subjects. It can be concluded that education is a central part in the pursuit of Human Security and Human Rights. It is the process of development of individuals throughout their lives, therefore, the environment also transforms people through experiences and examples, perspectives and stimuli – both negative and positive. It is necessary to use a quality educational process to form citizens who are aware of their rights and also of their duties, knowing how to mobilize them. It is observed that all these concepts are directly and inextricably related to the development of individuals, because it is only through the training of critical people, attentive to reality and sensitive to Human Security issues, that it will be possible to achieve a social state where Human Rights are really guaranteed to everyone.